Pengaruh investasi asing langsung, nilai tukar, dan inflasi terhadap pertumbuhan PDB negara-negara OKI dalam perspektif ekonomi Islam - Wati, Silvi Kesuma; Bahtiar, M. Yusuf; Kurniawan, Agus (STAI Auliaurrasyidin Tembilahan, 2025)
One of the main indicators for measuring a country's economic performance is GDP. This study aims to analyze the effect of foreign direct investment, exchange rates and inflation on GDP in OIC countries. This research method uses an Associative quantitative approach with a Panel Data Regression model. The population in this study is 57 OIC countries. The sample in this study was selected using Purposive Sampling Technique, using Secondary Data. Data were analyzed using Eviews10. The results of the study show that foreign direct investment and exchange rates have an insignificant effect on GDP while inflation has a significant effect on GDP in OIC, and simultaneously the three variables do not have a significant effect on OIC GDP.